Effect of Eggshell Sealing Methods on Embryonic Mortality and Hatchability in Cracked Broiler Eggs - Nwogwugwu, Chiemela Peter; Audu, Mercy Ochefije; Anjie, Sesugh Shadrach (FUDMA Journal of Sciences, 2026)
Eggshell cracking remains a major challenge in broiler hatchery operations due to its adverse effects on embryonic mortality and hatchability. This study evaluated the effectiveness of different eggshell sealing methods on embryonic mortality and hatchability of cracked broiler eggs. A total of 480 fertile broiler breeder eggs obtained from the National Animal Production Research Institute were used. The eggs were sourced from breeder hens aged 32 weeks and randomly assigned to four treatment groups: uncracked eggs (control), cracked eggs sealed with masking tape, nail cortex, and cellophane tape. Each treatment consisted of 120 eggs with five replicates of 24 eggs each in a completely randomized design. Eggs were incubated under standard conditions, and embryonic mortality and hatchability were determined. The results revealed significant differences (P < 0.05) among treatments. Embryonic mortality was lowest in the uncracked control and eggs sealed with cellophane tape, while masking tape recorded the highest mortality. Eggs sealed with nail cortex showed intermediate mortality. Similarly, hatchability was highest in the control and cellophane treated groups, moderate in nail cortex, and lowest in masking tape treated eggs. The superior performance of cellophane tape suggests its effectiveness in restoring eggshell integrity, maintaining moisture balance, and allowing adequate gaseous exchange necessary for embryonic development. In contrast, masking tape negatively affected embryo mortality, likely due to restriction of shell pore function and increased susceptibility to contamination. These findings suggest that cellophane tape is a practical and effective method for salvaging cracked broiler eggs, minimizing losses, and improving hatchery efficiency.
Keywords: Cracked Eggs; Embryonic Mortality; Hatchability; Eggshell Sealing; Broiler Chickens